Populasi, Ko-okurensi dan Preferensi Habitat Areca macrocalyx di Pulau Waigeo-Papua Barat - Widyatmoko, Didik (JURNAL BIOLOGI INDONESIA, 2015)
Research on population status, co-occurrence and habitat preference of the New Guinean palm Areca macrocalyx Zippelius ex Blume in hill forests of the Waigeo island (West Papua) was conducted in 2012 at six different habitat types: river bank, hill slope, hill top, intact, disturbed and converted forests. Population sizes varied spatially and were dominated by seedlings (62%) and juveniles (24%), indicating a growing population, in which recruitment and mortality were simultaneously continuous and density dependent. A. macrocalyx seemed to prefer specific habitats where river banks situated in the intact forest being the most suitable habitat. Although this palm still tolerated hill tops, the populations were suppressed and seemed to be sensitive to disturbance and changes in water table. A number of interrelating edaphic factors appeared to influence the abundance of this palm with a preference for well-drained soils with a high magnesium (Mg2+) content. High alkaline concentrations also corresponded to the density of the palm. Based on the association levels calculated using the Ochiai method, four tropical species (i.e. Licuala graminifolia, Tabernaemontana aurantiaca, Orania regalis, and Sommieria leucophylla) were positively associated with A. macrocalyx while ten other species were negatively associated. The palm tended to occupy sites with low-moderate C/N ratios where most sampled populations occurred in habitats with the average C/N values of lower than 10. Based on the r-squared values, exchangeable Mg2+ and Ca2+ appeared to have more influence on plant density and frequency than on canopy and basal area. Mortality was higher among the early growth stages but becoming very low in adult individuals. These findings suggest that edaphic factor is a determinant of the abundance and occurrence of the palm. To conserve the most important remaining populations, it is crucial to protect the most suitable sites and the existing-interconnected biotic factors in the reserve.ÃÂ ÃÂ Keywords: Areca macrocalyx, population, co-occurrence, habitat preference, Waigeo islandÃÂ